Please Help!!! Simplify (6x^-2)^2 (0.5x)^4 Show your work?

36 / 16 = 9 / 4

(6x^-2)^2 (0.5x)^4

= (6^2x^-4)((0.5)^4(x^4)

= (6^2)(0.5)^4(x^-4)(x^4)

= (36)(1/16)x^0

= 36/16

= 9/4

= 2.25

The answer is 9/4 which is 2.25.

But note that this only works if x is not zero, since zero can’t have a negative exponent.

Please Help!!! Simplify (6x^-2)^2 (0.5x)^4 Show your work?

(6/x²)² (x/2)⁴ = (36/x⁴) * (x⁴ / 16) = (36/16) = 9/4

Also Read :   Spiagge isole della grecia per il topless?

Leave a Comment